Percutaneous Puncture of Flexor Sheath Ganglions: An Assessment of Recurrence - Najjaar, Azzaam (Division of Plastic and Reconstructive Surgery, 2021)
Background Flexor tendon sheath ganglions (FTSG) comprise up to 15% of hand ganglions. The management is split between two schools of practice: percutaneous puncture or surgical excision. The literature is equivocal as to which holds true superiority in terms of recurrence rates. The cost of surgical excision is higher and the recovery is longer. In addition, surgery also brings with it the potential for surgical complications, both immediate and long term. Percutaneous puncture can be performed at the time of the initial consult and an immediate return to normal activity with no down-time for the patient. The aim of this study is to assess the recurrence rate after percutaneous puncture. We also describe our employed technique. Method The technique for percutaneous puncture involved the use of a 25-gauge needle for ganglion puncture, no sclerosant or corticosteroid was injected, and an immediate post-procedure mobilisation protocol was employed. Patients were identified from clinical records and were followed up at a minimum of six months to check for recurrence. Results Eighteen patients were included in the study, 12 females and 6 males. The majority of FTSG were found to occur in the middle finger. Two patients experienced a recurrence. Both were successfully treated with a repeat puncture. No patients experienced a complication. Conclusion In our study, we show a low recurrence rate obtained with percutaneous puncture of FTSG using a simple technique. No complications were noted in our cohort on follow-up. We, therefore, recommend employing it as a first line treatment in the management of FTSG.